Annexin A2, autoimmunity, anxiety and depression. (September 2016) - Weiss, R.; Bitton, A.; Ben Shimon, M.; Elhaik Goldman, S.; Nahary, L.; Cooper, I.; Benhar, I.; Pick, C.G.; Chapman, J.
Abstract: Objectives: Antiphospholipid syndrome (APS) is associated with neurological manifestations and one of the novel autoantigens associated with this disease is Annexin A2 (ANXA2). In this work we have examined the effect of high levels of autoantibodies to ANXA2 on the brain in a mouse model. Methods: Recombinant ANXA2 emulsified in adjuvant was used to immunize mice while mice immunized with adjuvant only served as controls. At peak antibody levels the animal underwent behavioral and cognitive tests and their brains were examined for ANXA2 immunoglobulin G (IgG) and expression of ANXA2 and the closely linked protein p11. Results: Very high levels of anti-ANXA2 antibodies (Abs) were associated with reduced anxiety in the open field 13.14% ± 0.89% of the time in the center compared to 8.64% ± 0.91% observed in the control mice (p < 0.001 by t-test). A forced swim test found significantly less depression manifested by immobility in the ANXA2 group. The changes in behavior were accompanied by a significant reduction in serum corticosteroid levels of ANXA2 group compared to controls. Moreover, higher levels of total IgG and p11 expression were found in ANXA2 group brains. Lower levels of circulating anti-ANXA2 Abs were not associated with behavioral changes. Conclusions: We have established an animal model with high levels of anti-ANXA2 Abs which induced IgG accumulation in the brain and specific anxiolytic and anti-depressive effects. This model promises to further our understanding of autoimmune disease such as APS and to provide better understanding of the role of the ANXA2-p11 complex in the brain. Highlights: This is the first animal model for the effects of anti-ANXA2 autoantibodies. Anti-ANXA2 Abs are associated with behavioral changes but not cognitive. These behavioral changes were accompanied by increased levels of Abs in the brain. The effect of Anti-ANXA2 autoantibodies on behavior is transient.